Recent Advances in the Synthesis of Borinic Acid Derivatives - Marion Boyet; Laurent Chabaud; Mathieu Pucheault (Molecules, 2023)
Borinic acids [R2B(OH)] and their chelate derivatives are a subclass of organoborane compounds used in cross-coupling reactions, catalysis, medicinal chemistry, polymer or optoelectronics materials. In this paper, we review the recent advances in the synthesis of diarylborinic acids and their four-coordinated analogs. The main strategies to build up borinic acids rely either on the addition of organometallic reagents to boranes (B(OR)3, BX3, aminoborane, arylboronic esters) or the reaction of triarylboranes with a ligand (diol, amino alcohol, etc.). After general practical considerations of borinic acids, an overview of the main synthetic methods, their scope and limitations is provided. We also discuss some mechanistic aspects.